2018
DOI: 10.1016/j.drugalcdep.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

An improved model of ethanol and nicotine co-use in female P rats: Effects of naltrexone, varenicline, and the selective nicotinic α6β2* antagonist r-bPiDI

Abstract: Background: Although pharmacotherapies are available for alcohol (EtOH) or tobacco use disorders individually, it may be possible to develop a single pharmacotherapy to treat heavy drinking tobacco smokers by capitalizing on the commonalities in their mechanisms of action. Methods: Female alcohol-preferring (P) rats were trained for EtOH drinking and nicotine self-administration in two phases: (1) EtOH alone (0 vs. 15% EtOH, 2-bottle choice) and (2) concomitant access, during which EtOH access continued with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…; Tizabi et al , ; Truitt et al ). Multiple reports have indicated that naltrexone and varenicline, the pharmacological ‘gold standards’ for treating AUD and nicotine dependence, both fail to alter the concurrent co‐administration of EtOH+NIC (Van Skike et al ; Waeiss, Knight, Hauser et al ; Maggio et al ). The current results provide clear preclinical data indicating that EtOH+NIC co‐administration results in a unique neurological cascade that is not observed following comparable exposure to EtOH or NIC alone.…”
Section: Discussionmentioning
confidence: 99%
“…; Tizabi et al , ; Truitt et al ). Multiple reports have indicated that naltrexone and varenicline, the pharmacological ‘gold standards’ for treating AUD and nicotine dependence, both fail to alter the concurrent co‐administration of EtOH+NIC (Van Skike et al ; Waeiss, Knight, Hauser et al ; Maggio et al ). The current results provide clear preclinical data indicating that EtOH+NIC co‐administration results in a unique neurological cascade that is not observed following comparable exposure to EtOH or NIC alone.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of Var and Nal (and the specific α6β2* antagonist r-bPiDI) to alter concurrent EtOH (oral) +NIC (i.v.) self-administration has been replicated in a novel model that increases intake levels of both drugs (Maggio et al, 2018b). Therefore, consistent preclinical data has indicated that Var is not effective at reducing EtOH +NIC co-administration.…”
Section: Discussionmentioning
confidence: 95%
“…α 6 β 2* nAChRs are limitedly distributed in dopaminergic cells in the mesocorticolimbic. Previous studies have reported that α 6/ α 3 β 2 β 3 nAChRs antagonists can inhibit drug addiction such as nicotine, alcohol, and cocaine ( Brunzell et al, 2010 ; Kamens et al, 2017 ; Maggio et al, 2018 ; Avelar et al, 2019 ). However, the role of α 6β2* nAChRs in morphine addiction has not been verified so far.…”
Section: Discussionmentioning
confidence: 99%